Anisotropic viscoelasticity and molecular diffusion in nematic wormlike micelles. Issue 6 (3rd May 2018) - Wilmsmeyer, Kyle G.; Li, Xiuli; Madsen, Louis A.
ABSTRACT: Using rheo-NMR, pulsed-field-gradient NMR diffusometry and solution rheology, we observe temperature- and composition-dependent orientational order as well as director dynamics and molecular transport in a nematic wormlike micelle (WLM) system composed of cetyltrimethylammonium bromide in D2 O. We measure, for the first time over a comprehensive nematic range in WLMs, four of the five independent anisotropic viscosities by fitting nonlinear rheo-NMR director realignment data and comparing with traditional solution rheology measurements. Additionally, we extract self-diffusion coefficients in three orthogonal directions for the aligned WLM unimers as well as for the D2 O solvent molecules. Continued study and enhanced understanding of complex fluid dynamics in these anisotropic shear-modulated fluid systems can lead to advances in lubricants, coatings, oil extraction, drug delivery and tissue engineering. GRAPHICAL ABSTRACT: